Optimalisasi Penerapan Media Pembelajaran IPA Sebagai Sarana Mewujudkan Pembelajaran Bermakna di SDN Pandian I - Siti Aisyah; Ayu Fitriya Ramadani; Anggita Eka Wulandari; Moh Rafi Rizqullah; Yeni Puji Astuti (LPPM Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Bojonegoro, 2025)
Science learning in elementary schools requires the use of instructional media to help students understand abstract concepts. However, media utilization is still not optimal due to limited teacher creativity and inconsistent use of learning aids. This study aims to describe the optimization of instructional media in science learning at SDN Pandian I to create meaningful learning experiences. A qualitative method was employed through structured interviews and observations of teachers and media use in the classroom. The findings show that the school provides various media such as worksheets, posters, anatomical models, solar system models, microscopes, and science kits. These media effectively help students grasp concepts concretely, increase motivation, and encourage active participation. Nevertheless, some teachers rarely use them due to time and preparation constraints. Optimizing media use requires improving teacher competence and better lesson planning.